Analisis distruptive marketing pada perusahaan startup (PT. Gojek Indonesia) - Muttaqin, Ridlwan (Jurnal Kajian Manajemen Bisnis, 2020)
This study aims to obtain findings regarding the internal conditions of Gojek, obtain findings regarding Gojek's externalities, and obtain findings on the strategic results that Gojek needs to do in increasing service sales through the concept of Disruptive Marketing. The object of this research is PT. Indonesian Gojek. The variable in this study is Disruptive Marketing. This type of research is descriptive. With qualitative methods and SWOT analysis. Based on the overall research results with SWOT analysis shows that the direction of Go-Jek's management in increasing service sales through the concept of Disruptive Marketing is in a Stable Growth Strategy, meaning that Gojek is pursuing maximum growth by strengthening market share, pursuing profit, and this strategy is able to pursue growth. sustainable by always making innovations.